2017
DOI: 10.1007/s00125-017-4401-5
|View full text |Cite
|
Sign up to set email alerts
|

VLDL and apolipoprotein CIII induce ER stress and inflammation and attenuate insulin signalling via Toll-like receptor 2 in mouse skeletal muscle cells

Abstract: Aim/hypothesis Here, our aim was to examine whether VLDL and apolipoprotein (apo) CIII induce endoplasmic reticulum (ER) stress, inflammation and insulin resistance in skeletal muscle. Methods Studies were conducted in mouse C2C12 myotubes, isolated skeletal muscle and skeletal muscle from transgenic mice overexpressing apoCIII. Results C2C12 myotubes exposed to VLDL showed increased levels of ER stress and inflammatory markers whereas peroxisome proliferator-activated receptor γ co-activator 1α (PGC-1α) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…67 Additionally, incubation of myotubes with a neutralizing antibody against Toll-like receptor 2 (TLR2) abolished the effects of ApoCIII on ER stress, inflammation, and insulin resistance, indicating that the effects of ApoCIII are mediated by this receptor. 64 In summary, the ApoCIII-induced ER stress in skeletal muscles enhances expression of inflammatory mediators, and thus attenuates insulin signalling pathway. Moreover, the increase of hepatic lipid accumulation in the context of elevated plasma ApoCIII levels can lead to NAFLD, hepatic insulin resistance, and thus DM.…”
Section: Apociii-induced Insulin Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…67 Additionally, incubation of myotubes with a neutralizing antibody against Toll-like receptor 2 (TLR2) abolished the effects of ApoCIII on ER stress, inflammation, and insulin resistance, indicating that the effects of ApoCIII are mediated by this receptor. 64 In summary, the ApoCIII-induced ER stress in skeletal muscles enhances expression of inflammatory mediators, and thus attenuates insulin signalling pathway. Moreover, the increase of hepatic lipid accumulation in the context of elevated plasma ApoCIII levels can lead to NAFLD, hepatic insulin resistance, and thus DM.…”
Section: Apociii-induced Insulin Resistancementioning
confidence: 99%
“…Moreover, ER stress inhibits insulin signalling by inducing serine phosphorylation of insulin receptor substrate 1 (IRS‐1) and it also down‐regulates the insulin receptor levels in adipocytes . Additionally, incubation of myotubes with a neutralizing antibody against Toll‐like receptor 2 (TLR2) abolished the effects of ApoCIII on ER stress, inflammation, and insulin resistance, indicating that the effects of ApoCIII are mediated by this receptor …”
Section: Mechanisms Linking Apociii and Dmmentioning
confidence: 99%
See 1 more Smart Citation
“…VLDL exposure in muscle also resulted in an increase mRNA of IL-6, CMP1 and TNF-α, as well as IRS Ser 307 phosphorylation, and reduced IkBα [33], these data indicate that disruption of fatty acid handling in skeletal muscle can induce ER stress, insulin resistance and inflammation.…”
Section: Er Stress and Unfolded Protein Responsementioning
confidence: 56%
“…The non-alcoholic fatty liver disease (NAFLD) begins with hepatic steatosis, which is defined as the accumulation of triglycerides (TG) at the level of the cytoplasm, in histology is evidenced by the presence of droplets in cytoplasm of TG in more than 5% of the hepatocytes, steatosis may progress to a state of inflammation and cellular damage that may end in NAFLD and hepatic cirrhosis (6). In the pathogenesis of NAFLD it has been shown that the increase of free fatty acids leads to a deregulation of the ways of assimilation and release of free fatty acid in the liver, thus modifying the regulation of transcription of the genes of lipogenesis and their transport out of the liver (7,8). The excess of TG overloads the carrier VLDL molecules, so VLDL-TG of greater diameter that exceed the sinusoidal pores of epithelium accumulate in the liver, and may generate stress in the endoplasmic reticulum (ER) and the activation of the pathway NF-κB, which increase the transcription of genes encoding for pro-inflammatory cytokines (8,9).…”
Section: Introductionmentioning
confidence: 99%